Improving the methane aromatization activity and anti-carbon deposition on MCM-22 through nano α-MoO3 modification. (17th January 2023) - Hu, Jing; Yang, Chunxue; Liu, Bing; Zhao, Xinyu; Wang, Yin; Wang, Xiaohui; Liu, Jinglin; Guan, Jingqi
Abstract : Compared with commercial MoO3, α-MoO3 modified MCM-22 possesses more Mo species in the zeolite pores, more MoC x active sites, and fewer Brønsted acid sites. Abstract : Natural gas is considered to be an important energy and hydrocarbon feedstock. To overcome the harmful combustion of natural gas and convert it to high-value-added products, the development of efficient and stable catalysts via methane dehydroaromatization (MDA) is needed. Here, we use nano α-MoO3 to modify the MCM-22 zeolite for MDA, achieving a 13.3% methane conversion and a 9.1% yield of aromatics. Compared with commercial MoO3, the α-MoO3 modified MCM-22 possesses more Mo species in the zeolite pores, showing a higher catalytic activity, more MoC x active sites during MDA, exhibiting a higher benzene selectivity, and fewer Brønsted acid sites, leading to a strong anti-carbon deposition ability.